COMPARATIVE ANALYSIS OF PLATE GIRDER DESIGNS ON NON-COMPOSITE BRIDGES BETWEEN AASHTO LRFD BRIDGE DESIGN SPECIFICATIONS 2017 CODE WITH SNI 1729:2015 CODE - Donald Essen; Nurul Musyafa Ulul Hidayah (Neutron, 2020)
This study aims to the structural design of non-composite plate girders using AASHTO LRFD Bridge Design Specifications 2017 code compared to SNI 1729:2015 code. The span of the bridge used as the object of study is 40 meters with a width of 10 meters. In this study, plate girders are designed based on AASHTO code and SNI code, then also given the loading according to SNI 1725:2016 code, and in the analysis of the structure using CSi Bridge software to get the value of internal forces i.e. Moment Force (Mu) of 3595.38 kNm and Shear Force (Vu) of 449.9968 kNm. The results obtained from this study are the non-composite bridge plate girder designed with AASHTO LRFD Bridge Design Specifications 2017 and SNI 1729:2015 obtained the stability requirements of strong boundary conditions flexure design. Then obtained Nominal Moment value (ØMn) of 8016.843 kNm for AASHTO LRFD Bridge Design Specifications 2017 and Nominal Moment value (ØMn) of 6081.97 kNm for SNI 1729:2015. From the values obtained it can be concluded that the two regulations produce a safe and strong plan as per the applicable provisions namely Moment (Mu <ØMn).